Peptide-Based Physical Gels Endowed with Thixotropic Behaviour - Zanna, Nicola (Gels, 2017)
Thixotropy is one of the oldest documented rheological phenomenon in colloid science and may be defined as an increase of viscosity in a state of rest and a decrease of viscosity when submitted to a constant shearing stress. This behavior has been exploited in recent years to prepare injectable hydrogels for application in drug delivery systems. Thixotropic hydrogels may be profitably used in the field of regenerative medicine, which promotes tissue healing after injuries and diseases, as the molten hydrogel may be injected by syringe and then self-adapts in the space inside the injection site and recovers the solid form. We will focus our attention on the preparation, properties, and some applications of biocompatible thixotropic hydrogels.